The Index of Cognitive Activity - Eligibility for task-evoked informational strain and robustness towards visual influences. (April 2021) - Czerniak, Julia N.; Schierhorst, Nikolas; Villani, Valeria; Sabattini, Lorenzo; Brandl, Christopher; Mertens, Alexander; Schwalm, Maximilian; Nitsch, Verena
Abstract: Various researchers have proposed pupillometric indicators to assess a person's cognitive strain. However, to distinguish the variation of pupil light response from psychosensory pupil response in experimental field conditions is a challenge. The Index of Cognitive Activity (ICA) addresses this problem by wavelet separation. This research investigates the ICA's sensitivity for multiple level task-evoked cognitive activity and visual influences concerning informational work tasks. Objective and subjective measures assessed cognitive strain of participants ( N = 22) during various tasks. In a first experiment, mental arithmetic tasks were used to induce different levels of cognitive activity. In a second experiment, influences of screen polarity and presentation of information were investigated ( N = 18). The results indicate that eye metrics are rarely sensitive to slight variations in task difficulty. Moreover, the ICA is likely to be sensitive towards constant screen illumination and shows tendencies regarding changes in displayed information. Possible ramifications for the objective assessment of cognitive strain are discussed. Highlights: Index of Cognitive Activity was not sensitive to changes in task difficulty. Screen polarity had an effect on the Index of Cognitive Activity. Information presentation in negative polarity conditions had an effect on the Index of Cognitive Activity.